Struktura in luminiscentne lastnosti SnO2: Eu luminoforja - Županc Mežnar, Lea (Kovine zlitine tehnologije, 1995)
Orange phosphor SnOsub2:Eu which can be used in cathode-ray tubes and other low-voltage displays has been prepared and its properties evaluated. The sol-gel method has been used for the synthesis. SnOsub2 was doped with 1-20 mol% of europium. We studied structural, morphologic, photo- and cathodoluminescent characteristics of xerogels and powders prepared at different remperatures and in various atmospheres.
Keywords: kemijska tehnologija; luminofor; sinteza; elektrotehnika